From Anti-humanism to Post-humanism: Hermann Hesse's Steppenwolf (Konturen, 2014)
Hermann Hesse’s Steppenwolf (1927) can be regarded as a post-humanist novel for several reasons. It is post-humanist in a temporal sense because it engages with the nineteenth-century humanist legacy from a twentieth-century perspective. The novel’s brazen critique of traditional bourgeois values does not simply reject humanism and its philosophy of individual autonomy. It dislodges idealist concepts of wholeness and self-perfection and replaces them with a multi-perspectival view of a continuously changing human consciousness, an open-ended process toward an ever-elusive self-awareness. The protagonist of Hesse’s novel, Harry Haller, even though still heavily influenced by the humanist tradition, can no longer be viewed as a clearly defined individual personifying the Cartesian dichotomy of body and mind. On the contrary, Hesse’s novel depicts Haller’s gradual disillusionment with this idealist world view by giving a detailed account of the deconstruction of his personality – a personality that, as it turns out, does not consist of a spiritual essence but dissolves into an accumulation of acquired conventions, habits, cultural and philosophical traditions, even specific historical events and constellations. Yet Hesse’s attempt to go beyond a mere negation of humanist values implies transcending the humanist paradigm in many respects, including its form.This essay will focus on the novel’s subversion of the humanist tradition. It discloses how Hesse’s novel undermines universalist philosophical claims, regardless of whether they belong to the idealist or anti-idealist Nietzschean philosophy that heavily influenced both the protagonist and his author. In light of the novel’s dismantling of binary reasoning, foregrounded in the protagonist’s man-animal division, the essay challenges conventional wisdom among critics who regard Hesse’s literary works as traditionalist.